Assessing the Impact of Project Management on Safety Culture and Construction Site Accidents: Evidence from Field Surveys in Urban Projects (Journal of Asian Development Studies, 2025)
Construction remains one of the most hazardous industries globally, particularly in urban environments, where complex workflows, dense workforces, and dynamic site conditions increase the likelihood of accidents. Despite improved regulations, many construction sites continue to face recurring safety challenges, primarily influenced by managerial practices and organisational safety culture. This study aimed to assess the impact of project management practices on safety culture and construction site accidents in urban projects. A quantitative, cross-sectional design was adopted, and data were collected through a structured survey administered to 270 construction workers, supervisors, and project managers. Statistical analyses were performed using SPSS, including descriptive statistics, correlation analyses, regression modelling, and mediation analyses. The results revealed that project management practices were strongly and positively associated with safety culture (r = 0.71, p < 0.01) and significantly reduced accident frequency (r = –0.64, p < 0.01). Regression results confirmed that project management predicted 50% of the variance in safety culture and 41% of the variance in accidents. Mediation analysis indicated that safety culture partially mediated the relationship between project management and accident occurrence. These findings highlight that stronger managerial planning, leadership, risk assessment, and communication contribute directly and indirectly to safer construction environments.